Impact of harvest delay on the physiological and sanitary quality of Sorghum sp. seeds - Guimarães Martins, Antonio (2023)
Harvest delay can alter the physiological and sanitary quality of sorghum seeds due to the longer exposure time of seeds to adverse environmental conditions in the field. In this study, we investigated the impact of delayed Sorghum sp. harvest on the physiological and sanitary quality of seeds in four hybrids grown in the tropical soil of the Brazilian Cerrado region. Plants from four Sorghum sp. hybrids (IPA SUDAN 4202, BRS 658, BRS 810, and BRS 373) were grown and submitted to four seed harvest periods (0, 7, 14, and 21 days after stage 9 – seed physiological maturity). The treatments were arranged in a completely randomized block design in a 4 × 4 factorial, with four replicates. At each harvest period, the thousand-seed weight, water content, first count of the germination test, germination, seedling emergence, emergence speed index, seedling dry matter, accelerated aging, electrical conductivity, and sanitary quality of seeds were determined. Seeds of higher physiological and sanitary quality of the IPA SUDAN 4202 and BRS 658 sorghum hybrids can be obtained when the harvest is carried out up to 7 days after the physiological maturity stage. However, the delay in seed harvesting at 14 and 21 days after physiological maturity results in a higher incidence of Colletotrichum sp., Curvularia sp., Rhizoctonia sp., and Alternaria sp. on the seeds of these hybrids. Delaying the harvest of sorghum seeds from 7 days after the physiological maturity stage compromises seed vigor and viability and increases the incidence of pathogens.